Maxillary osteogenic distraction and comprehensive orthodontic treatment in a patient with Pfeiffer syndrome. A case report - Leiva, Noemí (2019)
Pfeiffer´s syndrome is an autosomal dominantly inherited craniosynostosis, its clinical features are both at craniofacial level and upper and lower limbs. The treatment must be carried out by a multidisciplinary team and represents a great challenge for health professionals. The aim of this article is to present the case of a teenage patient diagnosed with Pfeiffer´s syndrome, who had severe maxillary hypoplasia, class III malocclusion and negative overjet; treated by osteogenic distraction with a RED (rigid external distractor) associated with fixed orthodontic appliances. The results reached the patient’s therapeutic and esthetic expectations and showed stability at 20 months posttreatment.